Triggering Growth via Growth Initiation Factors in Nature: A Putative Mechanism for in situ Cultivation of Previously Uncultivated Microorganisms - Jung, Dawoon; Machida, Koshi; Nakao, Yoichi; Kindaichi, Tomonori; Ohashi, Akiyoshi; Aoi, Yoshiteru (Frontiers in Microbiology, 2021)
Most microorganisms resist cultivation under standard laboratory conditions. On the other hand, to cultivate microbes in a membrane-bound device incubated in nature (in situ cultivation) is an effective approach. In the present study, we applied in situ cultivation to isolate diverse previously uncultivated marine sponge-associated microbes and comparatively analyzed this method’s efficiencies with those of the conventional method. Then, we attempted to investigate the key and previously unidentified mechanism of growing uncultivated microorganisms by in situ cultivation focusing on growth triggering via growth initiation factor. Consequently, significantly more novel and diverse microbial types were isolated via in situ cultivation than by standard direct plating (SDP). We hypothesized that some of environmental microorganisms which resist cultivation are in nongrowing state and requiring “growth initiation factor” for the recovery and that can be provided from environments (in this study from marine sponge). According to the hypothesis, the effect of the sponge extract on recovery on agar medium was compared between strains derived from in situ and SDP cultivation. Adding small amounts of the sponge extracts to the medium elevated the colony-formation efficiencies of the in situ strains at the starvation recovery step, while it showed no positive effect on that of SDP strains. Conversely, specific growth rates or saturated cell densities of all tested strains were not positively affected. These results indicate that, 1) the sponge extract contains chemical compounds that facilitate recovery of non-growing microbes, these substances worked on the in situ strains, and 2) growth initiation factor in the sponge extract did not continuously promote growth activity but worked as triggers for regrowth (resuscitation from nongrowing state).